Risk factors for new vertebral fractures after percutaneous vertebroplasty or percutaneous kyphoplasty in the treatment of osteoporotic vertebral compression fractures - Yang, Wencheng; Zou, Kaiwei; Lin, Xuping; Yang, Yanfang; Chen, Tianpei; Wu, Xiuming; Wang, Xiaomeng; Liu, Qingjun; Huang, Chunhui; Su, Wanhan (Frontiers in Medicine, 2025)
ObjectThis study aims to conduct a prospective analysis of patients with osteoporotic vertebral compression fractures (OVCF) who underwent percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP), and further analyze the risk factors for new vertebral fracture following treatment.MethodsA prospective study was conducted from November 2020 to March 2022 at the First Hospital of Longyan City to select patients with OVCF who underwent treatment in the Department of Spinal Surgery. Data collection during the follow-up period focused on various factors that could potentially be associated with new vertebral fractures after PVP/PKP procedures. Patients were divided into two groups based on whether they experienced new vertebral fractures within two years after discharge: the new fracture group (n = 186) and the non-fracture group (n = 64), and statistical analysis was conducted accordingly.ResultsAll cases were followed up for 12 to 24 months, with an average of 14.7 months. Differential analysis revealed that age, diabetes, hemoglobin (HB), total protein (TP), serum albumin (ALB), b-C-terminal telopeptide of type I collage (β-CTX), 25-hydroxyvitamin D (25-OH-D3), number of fractured vertebrae, bone mineral density (BMD), regular exercise after discharge, anti-osteoporosis treatment after discharge, cross-sectional area (CSA), and fatty degeneration ratio (FDR) were associated with new vertebral fractures (all P < 0.05). Multivariate analysis showed that age (OR = 1.519, P = 0.032), diabetes (OR = 3.273, P = 0.048), and FDR (OR = 1.571, P = 0.027) were positively associated with the occurrence of new vertebral fractures, while bone mineral density (OR = 0.108, P = 0.044), 25-OH-D3 (OR = 0.871, P = 0.032), CSA (OR = 0.564, P = 0.009), regular postoperative exercise (OR = 0.259, P = 0.025), and osteoporosis treatment (OR = 0.291, P = 0.045) were negatively associated with the occurrence of new vertebral fractures.ConclusionPatients with osteoporosis fractures who are older, have poor glycemic control, lower bone mineral density, lower levels of 25-OH-D3, weaker paraspinal muscles, and higher fat infiltration are at increased risk of new vertebral fractures after undergoing PKP/PVP. On the other hand, maintaining regular physical activity and adhering to osteoporosis treatment can help prevent new vertebral fractures.